Pendampingan Guru PAUD Permata Barko dalam Pembuatan Alat Permainan Edukatif Berbasis Budaya Lokal - Ahmad Maududi (PT. Penerbit Riset Sadwa, 2025)
Mentoring programs for Early Childhood Education (ECE) teachers play a vital role in enhancing the quality of early childhood learning, particularly through the utilization of educational play tools grounded in local cultural contexts. This program aimed to strengthen the professional competencies of teachers at PAUD Permata Barko in designing, developing, and implementing learning media that are creative, safe, and contextually relevant, while simultaneously introducing local cultural values to young children. The mentoring process was implemented systematically through several stages, including the introduction of educational play tool concepts, material selection, production techniques, hands-on practice, media trials, and media evaluation. The educational play tools developed during the program included the Lombok Ikat Weaving Motif Puzzle, Sasak Traditional House Building Blocks, and Lombok Folklore Story Cards. These learning media were intentionally designed to stimulate children’s motor development, cognitive abilities, creativity, imagination, language skills, and social interaction. The findings indicate a notable improvement in teachers’ understanding and skills in developing educational play tools based on local culture, as well as the availability of sustainable educational play tool products that can be continuously utilized in early childhood learning activities. Furthermore, the results of this activity may serve as a model for sustainable mentoring initiatives in other early childhood education institutions seeking to develop creative, contextual, and innovative educational media rooted in local cultural values.